The Significant Impact Of Service Quality On Customer Satisfaction Specifically Based On The Quality Dimensions Observed In Perum Pegadaian - Nendi, Ikhsan; Koesharijadi, Koesharijadi; Abdurokhim, Abdurokhim (Politeknik APP Jakarta, 2024)
This study aims to determine the effect of service quality on satisfaction, with the research focusing on Perum Pegadaian in Malang City, East Java. The sampling technique employed involves multiple sampling using accidental and purposive sampling methods, resulting in a sample size of 100 pawnshop customers. The analysis method utilized is multiple linear regression. The t-test results for each service quality dimension reveal the following outcomes: (1) Physical evidence (tangible) does not have a significant effect on satisfaction, (2) Reliability does not significantly impact satisfaction, (3) Responsiveness does not have a significant effect on satisfaction, (4) Assurance significantly influences satisfaction, and (5) Attention also has a significant effect on satisfaction. Based on the F-test, it is concluded that all dimensions of service quality significantly affect satisfaction.